Determining the prevalence of depression among older adults living in Burdur, Turkey, and their associated factors. Issue 4 (29th January 2020) - Güzel, Aysun; Kara, Fatih
Abstract : Background: This study aimed to determine the prevalence of depression among older adults living in Burdur, Turkey, and their associated factors. Methods: This analytical cross‐sectional study was conducted between May 1, 2015 and August 20, 2015 comprising 35 339 subjects aged ≥65 years living in Burdur; the sample was 770 subjects identified using a population‐weighted cluster sampling method. Data were collected by using personal information forms, Geriatric Depression Scale, and the Older People's Quality of Life Scale of the World Health Organization. The statistical analysis was performed by using t ‐test for independent samples, one‐way analysis of variance and post hoc multiple comparison tests, Pearson correlation, and regression analysis. P  < 0.05 was considered as significant. Results: Of the study population, 51.8% had a score of ≥14 (definite depression). According to the regression model, the prevalence of depression was higher in older adults aged ≥85 years than in older adults aged 65–74 years ( P  < 0.01), in females than in males ( P  < 0.01), in individuals who never consumed alcohol than in those who consumed alcohol ( P = 0.04), and in older adults who perceived their health as poor than in those who were unsure about their health and perceived their health as good ( P  < 0.01). Correlation analysis showed a poor, negative, and significant correlation (r = −0.38; P  < 0.01) between the total scores of Older People's Quality of Life Scale of the World Health Organization and Geriatric Depression Scale. Conclusions: The prevalence of depression is high among older adults aged ≥65 years. Age, gender, alcohol consumption, health perception, and quality of life are important predictors of depression.